129I/127I RATIOS IN SURFACE WATERS OF THE ENGLISH LAKE DISTRICT - Atarashi-Andoh M.; Schnabel C.; Cook G.; MacKenzie A.B.; Dougans A.; Ellam R.M.; Freeman S.; Maden C.; Olive V.; Xu S.; Synal H.-A. (My University, 2007)
Accelerator Mass Spectrometry (AMS) was used to measure 129I/127I ratios in surface sea, lake, and river water samples collected in 2004 and 2005 from the English Lake District and from SW Scotland, areas which are in relatively close proximity to the Sellafield nuclear fuel reprocessing plant in NW England. The 129I/127I ratios in surface water collected from the shore of the Irish Sea were in the range 2.8 × 10-6 to 8.2 × 10-6. These ratios are one order of magnitude higher than that of seawater collected from the Irish Sea in 1992, correlating with the increase in 129I content of the Sellafield liquid effluent discharge over the last decade. The 129I/127I ratios in lakes in the Lake District were in the range 0.7 × 10-6 to 6.4 × 10-6 and decreased exponentially as a function of distance from Sellafield. Consideration of the relative variation of stable I concentrations and 129I/127I ratios suggests that Sellafield gaseous discharges may be the dominant source of 129I to the lakes. © 2006 Elsevier Ltd. All rights reserved.